Natural preparation of rice husk-derived silica and eggshell-derived calcium carbonate composite as a coating material for dental implant - Kareem , Rehab Aamer; Naji, Ghassan Abdul-Hamid (Journal of Baghdad College of Dentistry, 2022)
Background: The world is in front of two emerging problems being scarceness of virgin re-sources for bioactive materials and the gathering of waste production. Employment of the surplus waste in the mainstream production can resolve these problems. The current study aimed to prepare and characterize a natural composite CaO-SiO2 based bioactive material derived from naturally sustained raw materials. Then deposit this innovative novel bioactive coating composite materials overlying Yttria-stabilized tetragonal zirconia substrate. Mate-rials and method; Hen eggshell-derived calcium carbonate and rice husk-derived silica were extracted from natural resources to prepare the composite coating material. The manufac-tured powder was characterized via Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscope (FESEM), X-ray fluorescence (XRF), X-ray diffraction (XRD) and particle size analyzer. The bioactive composite was deposited through radiofre-quency (Rf) reactive magnetron sputtering overlying disc-shaped samples with a dimension of 10 mm diameter were prepared from partially sintered Yttria-stabilized tetragonal zirconia polycrystal (Y-TZP). Results: The particle size of the rice husk-derived ranged between (480.4 – 606.1) nm with a mean particle diameter of 541 nm. The eggshell derived calcium carbonate powder presented a particle size between (266.4-336) nm and a mean particle diameter of 299.9 nm. The XRD data revealed the crystalline nature and phase composition of the natural prepared calcium carbonate powder and demonstrate the monocrystalline nature of natural SiO2. FTIR spectrometer showed the emergence of novel spectra separated from the two innovative components. XRF analysis revealed that 99.4% of the rice husk is SiO2 while eggshell-derived powder is mainly composed of calcium oxide. Fe-SEM images of the coated zirconia exhibited average thickness of the natural CaCO3/SiO2 coat layer may reach to12.84 µ. Conclusion: The prepared composite derived from natural resource waste is suitable to be utilized as a coating material for ceramic dental implants with promising biological and mechanical properties.